A NEW ACCOUNT ON THE POTRAIT OF IBRAHIM ASMARAKANDI AND HIS SUFISM APPROACH IN ISLAMIZATION OF JAVA (State Islamic University (UIN) of Sunan Ampel Surabaya, 2017)
This paper tried to show that Ibrahim Asmarakandi is one of the important preachers in the early era of Islamization in Indonesia. In addition, since Samarkandi is originated from Samakand, the paper also tried to show the relation between Islam in Samarkand and Java in the 15 CE. Other important findings shown in the paper is that the islamization of Samarkandi has succeeded to the extent that it is accepted by both the common and elites. Interestingly, the Sufism is proven to be effective in his islamization effort. One of the key is his successful strategies, resulted from Sufism approach, is the tolerant attitudes towards other religions particularly Hindu as the biggest religion in Java at the time.